Edge-Cloud Synergy in Real-Time AI Applications : Opportunities, Implementations, and Challenges - Srinivas Chennupati, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article explores the synergistic integration of edge computing and cloud infrastructure in real-time artificial intelligence applications. The convergence of these complementary paradigms creates a powerful computational continuum that addresses fundamental challenges in data processing for time-sensitive applications. The article examines the theoretical framework underpinning edge-cloud architectures, including resource allocation mechanisms, computational offloading strategies, and bandwidth considerations. Through detailed case studies across autonomous vehicles, smart city infrastructure, and healthcare monitoring systems, we demonstrate how this integrated approach enhances performance metrics while reducing operational costs. The article further analyzes technical challenges including latency management, security vulnerabilities, resource allocation optimization, and privacy preservation, offering mitigation strategies for each. Finally, the article focused on orchestration frameworks, 5G integration, privacy-preserving AI techniques, and standardization opportunities, providing a comprehensive roadmap for researchers and practitioners in this rapidly evolving field.
Keywords: Edge-cloud Integration; Real-time Artificial Intelligence; Distributed Computing; Resource Optimization; Privacy-preserving Analytics